Repeated Famotidine Administration Results in a Diminished Effect on Intragastric pH in Dogs. (1st December 2016) - Tolbert, M.K.; Graham, A.; Odunayo, A.; Price, J.; Steiner, J.M.; Newkirk, K.; Hecht, S.
Abstract : Background: Famotidine is an acid suppressant commonly administered to dogs. Prolonged famotidine use in people results in decreased efficacy, but the effect in dogs is unknown. Hypothesis/Objectives: To compare the effect of repeated oral administration of famotidine or placebo on intragastric pH and serum gastrin in dogs. We hypothesized that famotidine would have a diminished effect on intragastric pH on day 13 compared to day 1. Animals: Six healthy adult colony Beagles. Methods: Randomized, 2‐factor repeated‐measures crossover design. All dogs received oral placebo or 1.0 mg/kg famotidine q12h for 14 consecutive days. Intragastric pH monitoring was used to continuously record intragastric pH on treatment days 1–2 and 12–13. Mean pH as well as mean percentage time (MPT) that intragastric pH was ≥3 or ≥4 were compared between and within groups by analysis of variance. Serum gastrin was measured on days 0, 3, and 12 for each treatment. Results: Continued administration of famotidine resulted in a significant decrease in mean pH, MPT ≥3, and MPT ≥4 ( P < .0001) on day 12 and 13. This resulted in a mean decrease in pH by 1.63 on days 12 and 13 compared to days 1 and 2. Furthermore, a mean decrease of MPT ≥3 and MPT ≥4 by 33 and 45% was observed for the same time period, respectively. Conclusions and Clinical Importance: Continued administration of famotidine results in a diminished effect on intragastric pH in dogs. Caution is advised when recommending long‐term, daily oral administration of famotidine to dogs.